Effect of the NYSC/MDGs/WAP agro-enterprise loan on beneficiaries well-being in South West Nigeria (2015)
A strong link exists between poverty and income, thus attainment of full employment by youths can reduce poverty, crimes, terrorism and prostitution. This study investigated the effect of NYSC/MDGs/WAP on the well-being of beneficiaries in Southwest, Nigeria. Simple random sampling technique was used to select 120 respondents (ex-corps members). Data were collected with a structured questionnaire and analysed using both descriptive (frequency and percentages) and inferential statistics (Chi-square and PPMC). The mean age of the respondents was 30.8 years, 67.5% were married with 3-5 family size, 73.3% were Christians and 73.3% were male. Those with B.Sc certificate were 46.7%, HND certificate 23.3%. Results indicate that 91.8% used the loan to start up a business, 89.2% engaged in agro-enterprises, with 35.8% into poultry production, 8.3% into beekeeping, while the remaining 10.8% diverted the loan into other businesses. Most of the respondents indicated training (89.2%) and self dependence (81.7%)as their benefit from the programme. Most severe contraint faced by respondents was inadequate credit facility/loan. However, 55.8% of the respondents had favourable attitude and 53.3% had high well-being status. Marital status was significantly related to well-being of respondents (r=0.045, p=0.023). Attitude (r=0,554, p=0.000) of beneficiaries, benefit derived (r=0.284, p=0.002) and constraint encountered (r=0.250, p=0.006) were significantly related to their well-being. Participants’ involvement in NYSC/MDGs/WAP was beneficial and it has positive effect on their well-being. To ensure sustainability, availability of land, creation of marketing opportunities and follow-up becomes imperative.